2020
DOI: 10.25115/ejrep.v18i50.2728
|View full text |Cite
|
Sign up to set email alerts
|

The role of social skills in burnout and engagement among university students

Abstract: Introduction. Social skills may prevent burnout and enhance engagement in students by increasing social support and improving relationships with peers and teachers. Method. This study explores the interrelation between self-reported social skills and experienced burnout and engagement among 351 university students (70.5% women, 29.5% men) in different study fields. The Study Burnout Inventory (SBI-9), the Utrecht Work Engagement Scale-Student (UWES-S) and a social skills questionnaire were utilised. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
7
0
3
Order By: Relevance
“…In addition, further research has demonstrated that academically resilient students are more likely to recover from acute and chronic school-related difficulties (i.e., school burnout). Indeed, they are more able to cope with overwhelming school tasks showing higher passion and determination than their low-resilient counterparts [ 2 , 29 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, further research has demonstrated that academically resilient students are more likely to recover from acute and chronic school-related difficulties (i.e., school burnout). Indeed, they are more able to cope with overwhelming school tasks showing higher passion and determination than their low-resilient counterparts [ 2 , 29 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existen estudios que contrastan con nuestros resultados como el realizado en España donde los puntajes obtenidos por las personas universitarias evidencian que lograron nivel alto en habilidades sociales y medio en bienestar psicólogo (Morales-Rodríguez et al, 2020). Otro estudio en Finladia, encontró que un grupo universitario reportó nivel medio de habilidades sociales (Kiema-Junes et al, 2020). En Estados Unidos, las personas universitarias (en su mayoría provenientes de Asia) mostraron puntaje promedio bajo en bienestar psicológico (Luo et al, 2019); mientras que, estudiantado de Chile y México reportaron nivel medio de bienestar psicológico con 69,1% y 37,1% respectivamente (Bolgeri Escorza et al, 2020;Delgado Domínguez et al, 2020).…”
Section: Discussionunclassified
“…In turn, a social strategy of being positively directed towards social relations and looking for social support and advice (high social optimism) has been found to predict lower levels of early career work burnout [2]. Moreover, higher education students' ability to build and use social resources has been shown to be associated with reduced risk of developing study burnout [17,18].…”
Section: Introductionmentioning
confidence: 99%